Prediction of Response to Chemoradiotherapy by Dynamic Changes of Circulating Exosome Levels in Patients with Esophageal Squamous Cell Carcinoma - Zhang C; Guo Z; Jing Z (International Journal of Nanomedicine, 2024)
Chuanfeng Zhang, Zhen Guo, Zhao Jing Department of Oncology, Zhejiang Hospital, Hangzhou, Zhejiang, 310013, People’s Republic of ChinaCorrespondence: Zhao Jing, Department of Oncology, Zhejiang Hospital, No. 12 Lingyin Road, Hangzhou, Zhejiang, 310013, People’s Republic of China, Tel +86-571-87377308, Email jz96329@163.comBackground: The exosomes‐based liquid biopsy represents a prospective biomarker for tumor screening, prognosis prediction, and tumor regression. This study aimed to isolate circulating exosomes (CEs) from plasma of the esophageal squamous cell carcinoma (ESCC) patients who received chemoradiotherapy through exosome detection method via the ultrafast-isolation system (EXODUS) and investigated the association between the dynamic changes of CE levels and therapeutic effect.Methods: We isolated and quantitatively analyzed CEs from plasma of locally advanced ESCC patients received chemoradiotherapy at 2 time points: baseline (pre-chemoradiotherapy) and 2 months after the chemoradiotherapy (post-chemoradiotherapy). We isolated exosomes from plasma by EXODUS platform and confirmed them through nanoparticle tracking analysis (NTA), transmission electron microscope (TEM), and Western blot. The associations of CE level with clinicopathological characteristics, tumor regression, and progression-free survival (PFS) were analyzed.Results: The average diameter of CEs was 107.4± 14.3 nm at baseline and 101.7± 17.1 nm at post-chemoradiotherapy. The mean exosome concentration significantly decreased after chemoradiotherapy (7.3× 1011 particles/mL vs 5.4× 1011 particles/mL, P < 0.001). The patients with stage III–IVA and tumor length ≥ 5cm had obviously higher baseline CE levels. Dynamic changes in CE levels were successfully applied for evaluation of chemoradiotherapy response and PFS. Furthermore, through multivariate Cox regression analysis, it was revealed that dynamic changes of CE levels were an independent predictor of PFS in locally advanced ESCC patients who received chemoradiotherapy.Conclusion: Here, we demonstrated EXODUS platform isolated and enriched CEs from plasma of ESCC patients with high-purity and high-yield. The EXODUS platform can facilitate liquid biopsy based on exosomes translation to the clinic. Baseline CE levels can reflect ESCC tumor burden. The dynamic changes of CE levels during chemoradiotherapy allow the prediction of treatment effect and PFS of ESCC patients, requiring further investigations in larger patient cohorts.Keywords: exosomes, EXODUS platform, locally advanced ESCC, chemoradiotherapy